The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.lanepe.2021.100120
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreaks following full reopening of primary and secondary schools in England: Cross-sectional national surveillance, November 2020

Abstract: Background The full reopening of schools in September 2020 was associated with an increase in COVID-19 cases and outbreaks in educational settings across England. Methods Primary and secondary schools reporting an outbreak (≥2 laboratory-confirmed cases within 14 days) to Public Health England (PHE) between 31 August and 18 October 2020 were contacted in November 2020 to complete an online questionnaire. Interpretation There were 969 school o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
2
36
1
Order By: Relevance
“…The UK experience following full reopening of all school years in the autumn term was different to the partial reopening of some primary and secondary school years in the previous summer mini-term [7]. Nationally, SARS-CoV-2 infection rates were higher across all age-groups including children, and there were more infections and outbreaks reported in educational settings during the autumn term [9,19]. Using the same methodology in primary schools, the SARS-CoV-2 antibody seroconversion rate was 5% among staff and students [20], and a lower proportion of primary schools than secondary schools experienced a COVID-19 outbreak during the first half of the autumn term.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The UK experience following full reopening of all school years in the autumn term was different to the partial reopening of some primary and secondary school years in the previous summer mini-term [7]. Nationally, SARS-CoV-2 infection rates were higher across all age-groups including children, and there were more infections and outbreaks reported in educational settings during the autumn term [9,19]. Using the same methodology in primary schools, the SARS-CoV-2 antibody seroconversion rate was 5% among staff and students [20], and a lower proportion of primary schools than secondary schools experienced a COVID-19 outbreak during the first half of the autumn term.…”
Section: Discussionmentioning
confidence: 96%
“…), which in-turn will have a small but measurable impact on the reproduction number for SARS-CoV-2 [21]. There is, however, increasing evidence that the risk of SARS-CoV-2 transmission within school premises is very low, [22À24] especially among students [19]. In North Carolina, for example, surveillance of 11 school districts with more than 90,000 students and staff attending school in-person for 9 weeks, found 773 community-acquired SARS-CoV-2 infections, while contact tracing found only 32 additional infections that were acquired within school [24].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that reopening schools was associated with increases in transmission [ 43 ]. Moreover, cases of children testing positive for SARS-CoV-2 have risen following the reopening of schools [ 44 , 45 ]. In the 1 month ending 18 June, 2021, 181 SARS-CoV-2 outbreaks were confirmed in the UK related to primary and secondary schools [ 13 ].…”
Section: Role Of Children In Sars-cov-2 Transmissionmentioning
confidence: 99%
“…Weekly test positivity data reported by ONS and UKHSA showed a marked rise in positivity rate among secondary school-aged children over this period [8,9]. A similar rise was seen at the start of the previous (2020/21) academic year in England [10], however, the magnitude of the rise has been more pronounced this year. The differences could in part be attributable to increased transmissibility of the SARS-CoV-2 Delta (Phylogenetic Assignment of Named Global Outbreak (Pango) lineage designation B.1.617.2 and AY.…”
Section: Discussionmentioning
confidence: 80%